Impact of Large Granular Lymphocyte Leukemia on Blood DNA Methylation and Epigenetic Clock Modeling in Fischer 344 Rats. Issue 5 (28th October 2021) - Finesso, Giovanni E; McDevitt, Ross A; Roy, Roshni; Brinster, Lauren R; Di Francesco, Andrea; Meade, Theresa; de Cabo, Rafael; Ferrucci, Luigi; Perdue, Kathy A
Abstract: Age-dependent differences in methylation at specific cytosine–guanine (CpG) sites have been used in "epigenetic clock" formulas to predict age. Deviations of epigenetic age from chronological age are informative of health status and are associated with adverse health outcomes, including mortality. In most cases, epigenetic clocks are performed on methylation from DNA extracted from circulating blood cells. However, the effect of neoplastic cells in the circulation on estimation and interpretation of epigenetic clocks is not well understood. Here, we explored this using Fischer 344 (F344) rats, a strain that often develops large granular lymphocyte leukemia (LGLL). We found clear histological markers of LGLL pathology in the spleens and livers of 27 out of 61 rats aged 17–27 months. We assessed DNA methylation by reduced representation bisulfite sequencing with coverage of 3 million cytosine residues. Although LGLL broadly increased DNA methylation variability, it did not change epigenetic aging. Despite this, the inclusion of rats with LGLL in clock training sets significantly altered predictor selection probability at 83 of 121 commonly utilized CpG sites. Furthermore, models trained on rat samples that included individuals with LGLL had greater absolute age error than those trained exclusively rats free of LGLL (39% increase; p < .0001). We conclude that the epigenetic signals for aging and LGLL are distinct, such that LGLL assessment is not necessary for valid measures of epigenetic age in F344 rats. The precision and architecture of constructed epigenetic clock formulas, however, can be influenced by the presence of neoplastic hematopoietic cells in training set populations.